Programación neurolingüística Concepto y aplicaciones en la Organización (2014)
The article presents the views of the author and some concepts, such as on communication techniques in NLP (Neurolinguistics Programming), in order that this knowledge may disclose executives and companies operate, so let NLP can influence our daily lives, both personal and professional improvement.